EFFECTIVE UTILIZATION OF SOLAR ENERGY IN SUSTAINABLE AGRICULTURAL IRRIGATION A Provincial Example from Turkiye - Bingol, Ali; Arslan, Omer (Vinca Inst Nuclear Sci, 2023)
Food supply security is one of the most important problems facing the world today. Although fertile agricultural lands are decreasing day by day due to climate change caused by global warming, the demand for food is increasing with the increasing population from around the world. In addition, energy input costs in food production are increasing day by day. One of the energy input costs is the energy spent for agricultural irrigation. Meeting the energy required for agricultural irrigation from the Sun will both prevent environmental problems caused by fossil fuels and reduce agricultural irrigation costs. In this study, the province of Mus, which is one of the least developed cities in Turkey, with a high potential for agriculture and solar energy, is considered as a case study. In this study, firstly, the equipment that can be used in the solar-powered irrigation system was determined, after the necessary formulas and calculations were made in detail, finally, the cost analysis of this irrigation system was made and the time that the system could pay for itself was calculated. With this study, when the size of a field and the distance of the water source from the field are known, the required water pump size, PV panel size and installation cost can be easily calculated. Thus, a tool has been developed that can be easily used by every farmer. It is believed that this program will make a great contribution to encouraging farmers to engage in irrigated agriculture by utilizing solar energy.
Keywords: Mus plain; renewable energy; solar energy; irrigated agriculture; water pumps; sustainable agriculture